A Unique ATPase, ArtR (PA4595), Represses the Type III Secretion System in Pseudomonas aeruginosa - Kong, Weina; Dong, Mengmeng; Yan, Rong; Liang, Qingqing; Zhang, Huiqun; Luo, Wei; Zhang, Yani; Liang, Haihua; Duan, Kangmin (Frontiers in Microbiology, 2019)
Pseudomonas aeruginosa is an important human pathogen which uses the type III secretion system (T3SS) as a primary virulence factor to establish infections in humans. The results presented in this report revealed that the ATP-binding protein PA4595 (named ArtR, a Regulator that is an ATP-activated Repressor of T3SS) represses T3SS expression in P. aeruginosa. The expression of T3SS genes, including exoS, exoY, exoT, exsCEBA and exsD-pscB-L, increased significantly when artR was knockout. The effect of ArtR on ExsA is at the transcriptional level, not at the translational level. The regulatory role and cytoplasm localization of ArtR suggest it belongs to the REG sub-family of ATP-binding cassette (ABC) family. Purified GST-tagged ArtR showed ATPase activity in vitro. The conserved aspartate residues in the dual Walker B motifs prove to be essential for the regulatory function of ArtR. The regulation of T3SS by ArtR is unique, which does not involve the known GacS/A-RsmY/Z-RsmA-ExsA pathway or Vfr. This is the first REG subfamily of ATP-binding cassette that is reported to regulate T3SS genes in bacteria. The results specify a novel player in the regulatory networks of T3SS in P. aeruginosa.